Bevacizumab for acute neurologic deterioration in patients with glioblastoma. (September 2013) - Kaley, Thomas; Nolan, Craig; Carver, Alan; Omuro, Antonio
SUMMARY  Aim: Glioblastoma causes neurologic dysfunction owing to the tumor's location and peritumoral edema. Bevacizumab improves symptoms and steroid dependence, and may rescue glioblastoma patients hospitalized for acute neurologic dysfunction, allowing them to return home for outpatient treatment.Materials & methods: We carried out a retrospective review of glioblastoma patients with severe neurologic dysfunction who received bevacizumab as inpatients.Results: Nine patients (median age: 51 years; median Karnofsky Performance Status [KPS]: 40%) received one dose of bevacizumab while admitted for neurologic deterioration. Seven patients were treated at recurrence, two at diagnosis. Six patients clinically improved and continued outpatient treatment, while five decreased/discontinued dexamethasone.Conclusion: Single bevacizumab treatment administered to naive hospitalized patients with glioblastoma improves function and quality of life through avoidance of prolonged hospitalization and rehabilitation admissions, and decreased dexamethasone administration.